Design of a Wideband Quad-Polarization Reconfigurable Patch Antenna Array Using a Stacked Structure - Hu, Jun; Hao, Zhang-Cheng; Hong, Wei (IEEE transactions on antennas and propagation, 2017)
In this paper, a wideband stacked patch antenna array composed of four linearly polarized antenna elements is proposed for the implementation of four polarization reconfigurable states, i.e., vertical linear polarization (LP), horizontal LP, left-hand circular polarization, and right-hand circular polarization. A double-layer structure, including a driven substrate integrated waveguide (SIW) cavity and four parasitic radiation patches, is used to develop the wideband antenna element. The parasitic radiation patches are excited by etching a ring slot on the top surface of the SIW cavity, which has two diagonal ports fed by grounded coplanar waveguide lines. A 180° phase-shifting is achieved for polarization reconfigurable applications by individually feeding the antenna element with the two diagonal ports. A prototype operating at 5.7 GHz is fabricated and tested for the demonstration of the polarization reconfigurable capability. The measured results show that both the 10-dB impedance bandwidths and the 3-dB axial ratio bandwidths are wider than 5.19-6.1 GHz for the linear and circular polarization states. The measured maximum gains of the antenna array are 9.85 dBic and 10.1 dBi for the circular polarization states and the LP states, respectively. Experimental results show good agreement with simulated results, which indicate a good performance of the proposed patch antenna array.